2021
DOI: 10.1111/1365-2435.13825
|View full text |Cite
|
Sign up to set email alerts
|

Above‐ and below‐ground complementarity rather than selection drive tree diversity–productivity relationships in European forests

Abstract: Biodiversity experiments have identified both complementarity and selection as important drivers of the relationship between biodiversity and ecosystem functioning. However, their relative importance in above‐ and below‐ground ecosystem compartments of mature forests remains yet to be explored. We adopted a trait‐based approach to partition biodiversity effects in above‐ and below‐ground complementarity and selection. This approach was based on canopy and root traits measured in single‐ and mixed‐species plots… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 93 publications
2
17
0
Order By: Relevance
“…As a result, selection effects decreased after four years in our experiment, while complementarity effects continued to increase. This is in line with previous findings showing that selection effects play a major role at the beginning, but are replaced by complementarity effects after some time (Fargione et al, 2007;Jing et al, 2021;Lasky et al, 2014). Overall, our results support the hypothesis that co-occurring species in high-diverse temperate forests differ in niches and competitive abilities, which leads to strong biodiversity effects and higher productivity in mixtures compared to their monospecific counterparts Huang et al, 2018;Morin et al, 2011;Urgoiti et al, 2022).…”
Section: Discussionsupporting
confidence: 93%
“…As a result, selection effects decreased after four years in our experiment, while complementarity effects continued to increase. This is in line with previous findings showing that selection effects play a major role at the beginning, but are replaced by complementarity effects after some time (Fargione et al, 2007;Jing et al, 2021;Lasky et al, 2014). Overall, our results support the hypothesis that co-occurring species in high-diverse temperate forests differ in niches and competitive abilities, which leads to strong biodiversity effects and higher productivity in mixtures compared to their monospecific counterparts Huang et al, 2018;Morin et al, 2011;Urgoiti et al, 2022).…”
Section: Discussionsupporting
confidence: 93%
“…Over-yielding reflects substantial rooting plasticity in response to neighbors (Schmid and Kazda 2005 ; Bolte and Villanueva 2006 ). Several studies have confirmed that variation in root traits as the diversity of neighbors increases leads to niche differentiation and complementary colonization of underground space, thus promoting soil resource acquisition and reducing the competitive pressure among neighbors (Brassard et al 2013 ; Mueller et al 2013 ; Ma and Chen 2017 ; Jing et al 2021 ). Studies also have revealed evidence of interactive effects between nutrients and neighbors where some plants increase their root production in the presence of competition from neighbors (Mommer et al 2010 ; Padilla et al 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another hypothesis is the selection probability effect, which proposes that higher species richness improves productivity by increasing the chances of possessing high-yielding species (Špaèková and Lepš 2001 ; Schmid et al 2008 ). Most research on the relationship between plant species diversity and root productivity has tended to support the complementarity effect rather than the selection probability effect (Brassard et al 2011 ; Zeng et al 2020 ; Jing et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Mean annual cloud cover was compiled from the global 1-km cloud cover project (Wilson and Jetz, 2016). The standardized residuals were then used in the SEM analyses (Desie et al, 2020;García-Palacios et al, 2018;Jing et al, 2021). In addition, plant species responses to environmental changes can shift throughout their range, and many regional ecological indicator value systems have been developed in Europe, each with a different ordinal scale, spanning different environmental gradients and their own region of application (Diekmann, 2003).…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Complementarity is often considered as one of the fundamental mechanisms responsible for the positive effects of tree species diversity on forest primary productivity (a frequently measured component of ecosystem functioning) (Barry et al, 2019;Jing et al, 2021;Scherer-Lorenzen, 2014;Trogisch et al, 2017). For instance, complementarity in resource uptake ensures a higher amount of resources captured and thus a higher productivity (Forrester and Bauhus, 2016).…”
Section: Introductionmentioning
confidence: 99%